The performance of missing transverse momentum reconstruction and its significance with the ATLAS detector using 140 $$\hbox {fb}^{-1}$$ fb - 1 of $$\sqrt{s}=13$$ s = 13 TeV pp collisions - G. Aad; E. Aakvaag; B. Abbott; K. Abeling; N. J. Abicht; S. H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; B. S. Acharya; C. Adam Bourdarios; et al. (European Physical Journal C: Particles and Fields)
Abstract This paper presents the reconstruction of missing transverse momentum ( $$p_{\text {T}}^{\text {miss}}$$ p T miss ) in proton–proton collisions, at a center-of-mass energy of 13 TeV. This is a challenging task involving many detector inputs, combining fully calibrated electrons, muons, photons, hadronically decaying $$τ $$ τ -leptons, hadronic jets, and soft activity from remaining tracks. Possible double counting of momentum is avoided by applying a signal ambiguity resolution procedure which rejects detector inputs that have already been used. Several $$p_{\text {T}}^{\text {miss}}$$ p T miss ‘working points’ are defined with varying stringency of selections, the tightest improving the resolution at high pile-up by up to 39% compared to the loosest. The $$p_{\text {T}}^{\text {miss}}$$ p T miss performance is evaluated using data and Monte Carlo simulation, with an emphasis on understanding the impact of pile-up, primarily using events consistent with leptonic Z decays. The studies use $$140~\text {fb}^{-1}$$ 140 fb - 1 of data, collected by the ATLAS experiment at the Large Hadron Collider between 2015 and 2018. The results demonstrate that $$p_{\text {T}}^{\text {miss}}$$ p T miss reconstruction, and its associated significance, are well understood and reliably modelled by simulation. Finally, the systematic uncertainties on the soft $$p_{\text {T}}^{\text {miss}}$$ p T miss component are calculated. After various improvements the scale and resolution uncertainties are reduced by up to $$76%$$ 76 % and $$51%$$ 51 % , respectively, compared to the previous calculation at a lower luminosity.